ANALYSIS OF STUDENTS’ RESPONSE OF THE IMPLEMENTATION OF RMS (READING, MIND MAPPING, AND SHARING) LEARNING MODEL IN PHILOSOPHY OF SCIENCE - Muhlisin, Ahmad (Unnes Science Education Journal, 2018)
The purpose of this study is to describe the student's response towards the implementation of RMS learning model (Reading, Mind Mapping, and Sharing) in Philosophy of Science Learning. Type of research used is pre-experimental design. The research sample is 40 students from the first odd semester in the year of 2017/2018. The technique of analysing data used is quantitative descriptive. The result of the research shows that student response after implementation of RMS learning model gave the positive response of 92.5%. The highest student response indicator is on attention aspect with an average of 32, and the lowest on the satisfaction aspect with an average of 23.5.